Bacterial communities profiles of soil in Hulu Langat recreational parks, Selangor - Ahmad Mohiddin Mohd Ngesom; Asmalia Md Lasim; Faizul Akmal Abdul Rahim; Mardani Abdul Halim; Farah Shafawati Mohd-Taib (BMC Research Notes)
Abstract Objective Recreational Park soils with higher human disturbance harbor a more diverse bacterial communities, including genera associated with opportunistic pathogens. This raises concerns about the potential transmission of soil-borne diseases such as leptospirosis and melioidosis. Despite this, microbial compositions within specific environments remain poorly understood. This study investigates the diversity and profiles of bacterial communities across four recreational areas in Hulu Langat, Selangor, using 16 S rRNA gene metabarcoding. Results Results reveal diverse bacterial communities comprising 40 phyla, 93 classes, 173 orders, 251 families, and 346 genera across all sites. The most abundant phyla detected were Proteobacteria (42.84%), Acidobacteria (15.52%) and Actinobacteria (7.95%). All sampling sites exhibited a similar bacterial composition, but differences in abundance were observed based on the frequency of human disturbance. Network analysis revealed a strong association between Mycobacterium spp. and Streptomyces spp. with other taxa, suggesting their ecological importance and health implications. The results emphasize the importance of soil monitoring as a proactive measure to mitigate public health risks. Continuous surveillance, microbial risk assessments, and targeted intervention are recommended to mitigate soil-borne disease risks in recreational environments.